-36=8u+2(u-8)

Simple and best practice solution for -36=8u+2(u-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36=8u+2(u-8) equation:


Simplifying
-36 = 8u + 2(u + -8)

Reorder the terms:
-36 = 8u + 2(-8 + u)
-36 = 8u + (-8 * 2 + u * 2)
-36 = 8u + (-16 + 2u)

Reorder the terms:
-36 = -16 + 8u + 2u

Combine like terms: 8u + 2u = 10u
-36 = -16 + 10u

Solving
-36 = -16 + 10u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-10u' to each side of the equation.
-36 + -10u = -16 + 10u + -10u

Combine like terms: 10u + -10u = 0
-36 + -10u = -16 + 0
-36 + -10u = -16

Add '36' to each side of the equation.
-36 + 36 + -10u = -16 + 36

Combine like terms: -36 + 36 = 0
0 + -10u = -16 + 36
-10u = -16 + 36

Combine like terms: -16 + 36 = 20
-10u = 20

Divide each side by '-10'.
u = -2

Simplifying
u = -2

See similar equations:

| 7y+y+14=8y-4+3y | | 2a/3b-c= | | 4=-6v+8(v+2) | | -8x+4(x-3)=-8 | | 8y+8y=24 | | -5x+3=-47 | | -75+4x+6x=25 | | Y(2)+3y(2-1)=e(2) | | Y(1)+3y(1-1)=e(1) | | 5x-3x-19=11 | | 81+w=10w | | 12u=24+9u | | 5(3y-4)=10 | | 4s+3s-9s=22 | | 4=10m | | -6x-2x=48 | | Y(0)+3y(0-1)=e(0) | | 30=9m | | (-9p-1)-(-2p-5)= | | b/10=20 | | 6u=1+3 | | -7(-m-3)=46 | | 5(x+0.40)=5 | | 6x-6=-24+2x | | X+9+(-11)=2 | | (5-2i)/(1-3i) | | 56=5w+16 | | -2+3y=-23 | | 26=x/4-17 | | cot(10x)=cot(5x) | | 5x(4.1+b)=45 | | tan(10x)=tan(5x) |

Equations solver categories